PERANCANGAN MITIGASI RESIKO HUMAN ERROR AKTIVITAS MAINTENANCE PADA PT BATAM AERO TECHNIC - Setiawan, Hendri; Asmarawati, Citra (Computer Science and Industrial Engineering, 2022)
Potential errors can be avoided by controlling actions when carrying out maintenance with the aim of controlling work being a continuous corrective action. The problem faced by the company is human negligence or human error in the maintenance painting process. The method used is FMEA (Failure Mode and Effect Analysis) by providing an assessment of risk and mitigation plans using QRA. (Quantitative Risk Analysis) covers all activities to identify hazardous events sequentially and the level of risk. The research was conducted on the process of repainting the aircraft body. The purpose of the study was to determine the negligence of technicians or human error in the process of repainting the aircraft body and the factors causing the problem. The results of the study describe that the frequency of failure of the Boeing 737-900 Series painting process with the type of reject dust is 31.25. The results of the FMEA analysis on the failure of the Boeing 737-900 Series painting process with factors caused by human error, namely lack of maintenance and cleaning of work equipment after use has an RPN value of 448.